(untitled) (Pakistan Journal of Psychology, 2023)
With increased urbanization and industrialization, nearly all large cities of the world are facing the problems of transportation and traffic congestion. These issues not only have negative ecological and economical outcomes but also affect the mental and physical health of people. The current study aimed to explore the prevalence of psychological and pysical health issues associated traffic congestion. This study is exploratory in nature for which survey design was used. The sample of the study was 79 residents of Karachi who commute through various means of transportation on daily basis. The age of the participants ranged between 18-45 years; and the data was collected by using purposive sampling technique. Demographic Information Form and Self-Report Survey Questionnaire were employed on individual cases. Descriptive statistics were employed to analyze the data. The results revealed that a substantial portion of sample faces stress, anxiety and anger issues. Physical outcomes such as backache was also common along with decreased productivity at workplace. The implications of the findings and future directions are suggested.